High-Risk Culprit Plaque Predicts Cardiovascular Outcomes Independently of Plaque Rupture in ST-Segment Elevation Myocardial Infarction: Insight From Optical Coherence Tomography. (November 2022) - Wang, Ying; Zhao, Xiaoxiao; Zhou, Peng; Liu, Chen; Liao, Zhiyong; Wang, Xiaoqing; Yan, Shaodi; Sheng, Zhaoxue; Li, Jiannan; Zhou, Jinying; Chen, Runzhen; Chen, Yi; et al.
The present study explored the predictive value of culprit high-risk plaque (HRP) detected by optical coherence tomography (OCT) for predicting major adverse cardiovascular events (MACEs) in patients with ST-segment elevation myocardial infarction (STEMI). HRP was defined as the simultaneous presence of four criteria: minimum lumen area <3.5 mm 2, fibrous cap thickness <75 μm, lipid plaque with lipid arc extension >180°, and presence of macrophages. Patients (n = 274) were divided into non-HRP group (n = 206) and HRP group (n = 68). MACEs were defined as a composite of all-cause death, myocardial infarction, stroke, and revascularization. During a mean follow-up of 2.2 years, 47 (17.5%) MACEs were observed: 28 (13.6%) in the non-HRP group and 19 (27.9%) in the HRP group (log-rank P = .005). Patients with HRP were 2.05 times more likely to suffer from a MACE than those without HRP (hazards ratio: 2.05, 95% confidence interval: 1.04-4.02, P = .038); MACE risk was comparable between plaque rupture and plaque erosion. In conclusion, HRP was present in 24.8% of STEMI patients and associated with higher cardiovascular risk independent of plaque rupture, suggesting that HRP detected by OCT may help identify patients at high risk of future cardiac events.